Ascendancy of sex hormones on periodontium during reproductive life cycle of women - Ashutosh Nirola; Priyanka Batra; Jaspreet Kaur (Wolters Kluwer Medknow Publications, 2018)
Throughout the reproductive life cycle of women, fluctuating levels of sex hormones during puberty, menses, pregnancy, and menopause have direct and indirect effects on oral health and they also influence their susceptibility to periodontal disease. These physiological conditions are associated with an exaggerated inflammatory response without accompanying an increased plaque level. Changes in hormone levels also lead to alteration in the subgingival microflora, epithelial keratinization, decreased salivary flow, altered gingival crevicular fluid, effects on specific cells of periodontium and local immune system, burning sensation, halitosis, interproximal alveolar bone loss, and to a lesser extent, clinical attachment loss. The presence of maternal periodontitis has been associated with adverse pregnancy outcomes, such as preterm birth, preeclampsia, gestational diabetes, delivery of a small-for-gestational age infant, and fetal loss. The strength of these associations ranges from a 2-7-fold increase in risk. The increased risks suggested that periodontitis might be an independent risk factor for adverse pregnancy outcomes. Thus, the female body has a series of reaction to the hormonal changes seen within. Improper oral hygiene and hormonal imbalance seen during different life cycles of female patients exaggerate the oral tissue response to the plaque and other local factors, thus worsening the condition. Prevention is better than cure; hence, necessary precautions need to be taken at the earliest once the condition of the patient is known.